Utilization of Emergency Medical Service Increases Chance of Thrombolytic Therapy in Patients with Acute Ischemic Stroke - Hsieh, Ming-Ju (2013)
OBJECTIVE: To determine whether utilization of emergency medical service (EMS) can expedite and improve the rate of thrombolytic therapy administration in acute ischemic stroke patients. METHODS: This is a prospective observational study of consecutive patients presenting to the emergency department (ED) with an ischemic stroke within 72 hours of symptom onset. Variables associated with early ED arrival (within 3 hours of stroke onset), and administration of thrombolytic therapy were analyzed. We also evaluated the factors related to onset-to-needle time in patients receiving thrombolytic therapy. RESULTS: From January 1, 2010 to July 31, 2011, there were 1081 patients (62.3% men, age 69.6 ± 13 years) included in this study. Among them, 289 (26.7%) arrived in the ED within 3 hours, and 88 (8.1%) received intravenous thrombolytic therapy. Patients who arrived to the ED by EMS (n=279, 25.8 %) were independently associated with earlier ED arrival (adjusted odds ratio [OR] = 3.68, 95% confidence interval [CI] = 2.54 to 5.33), and higher chance of receiving thrombolytic therapy (adjusted OR = 3.89, 95% CI= 1.86 to 8.17). Furthermore, utilization of EMS decreased onset-to-needle time by 26 minutes in patients receiving thrombolytic therapy. CONCLUSION: Utilization of EMS can help acute ischemic stroke patients in early presentation to ED, facilitate thrombolytic therapy, and reduce the onset to needle time.